Prototype Equipment and Techniques for Obtaining Сavitation-Resistant Coatings To Be Applied fo Working Surfaces of Steam Turbine Blades Made of VT6 Titanium Alloy in Order to Replace Imported Counterparts - Bilous V.А.; Voyevodin V.М.; Khoroshikh, V.M.; Nosov, G.I.; Marinin, V.G.; Leonov, S.A.; Ovcharenko, V.D.; Kovalenko, V.I.; Komar, A.A.; Kuprin, A.S.; Shpagina L.О. (Science and Innovation, 2024)
Prototype equipment and techniques for obtaining the cavitation-resistant coatings to be deposited on the working surfaces of steam turbine blades made of VT6 titanium alloy have been designed and manufactured. The selection and of composition and conditions of synthesis of optimal coating for hardening the blades have been justified. The parameters of coatings deposition on the blade model have been found, the trial deposition of coatings has been made. The VT6 titanium alloy samples with the preferred coatings have been tested under simulated operational conditions. The coatings have been deposited on the blade model of up to 130 cm long and up to 30 kg heavy. The rate of TiN-based coating deposition was 10 μm/h.